2014
DOI: 10.1038/ejcn.2014.205
|View full text |Cite
|
Sign up to set email alerts
|

Comparative measurement of ghrelin, leptin, adiponectin, EGF and IGF-1 in breast milk of mothers with overweight/obese and normal-weight infants

Abstract: This study revealed that there was a correlation between ghrelin and EGF level in breast milk of mothers with obese and non-obese infants, suggesting a possible regulatory effect of these two hormones on weight in infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 26 publications
1
44
0
1
Order By: Relevance
“…Moreover, the majority of previous studies analysed leptin in skim HM in cross-sectional cohorts and are restricted to the first and third months postpartum [25], limiting their ability to determine leptin profiles during lactation in women of varying BC. Only three studies have analysed %FM using dual-energy X-ray absorptiometry (DXA) [24], skinfold measures [63] and bioelectrical impedance analysis [65] and they found a strong association between %FM and skim milk leptin, consistent with the results from our study. Interestingly, Khodabakhshi et al (2015) [65] found association between HM leptin and both %FM and BMI only in the subset of mothers of obese infants but not in the subset of mothers of normal infants, although these two groups did not differ by BMI or leptin concentration.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the majority of previous studies analysed leptin in skim HM in cross-sectional cohorts and are restricted to the first and third months postpartum [25], limiting their ability to determine leptin profiles during lactation in women of varying BC. Only three studies have analysed %FM using dual-energy X-ray absorptiometry (DXA) [24], skinfold measures [63] and bioelectrical impedance analysis [65] and they found a strong association between %FM and skim milk leptin, consistent with the results from our study. Interestingly, Khodabakhshi et al (2015) [65] found association between HM leptin and both %FM and BMI only in the subset of mothers of obese infants but not in the subset of mothers of normal infants, although these two groups did not differ by BMI or leptin concentration.…”
Section: Discussionsupporting
confidence: 90%
“… 1 Indeed, several studies have identified the associations between the concentration of these hormones in breast milk and subsequent infant weight and growth. 25 26 42 However, these finding are associations and may be explained by confounding factors.…”
Section: Discussionmentioning
confidence: 92%
“…An additional study also reported no significant correlation between maternal BMI and ghrelin concentration in breast milk . However, a recent study found an inverse association between maternal BMI and ghrelin concentration in breast milk . Overall, the evidence for an association between breast milk ghrelin and maternal factors, including maternal BMI, remains unclear.…”
Section: Bioactive Components In Breast Milkmentioning
confidence: 97%